Risk factors for sexually transmitted infections in women in rural Northeast Brazil - Fabíola Araújo Oliveira,1,2 Katrin Lang,3 Viola Ehrig,3 Jorg Heukelbach,1,2 Francisco Fraga,4 Marina Stoffler-Meilicke,5 Ralf Ignatius,3 Ligia Regina Franco Sansigolo Kerr,1 Hermann Feldmeier.3 (The Journal of Infection in Developing Countries, 2008)
Background: Sexually transmitted infections (STIs) are highly prevalent in northeast Brazil, but factors associated with the presence of an STI have rarely been studied systematically.Methodology: We performed a population-based study to assess factors associated with STIs in women of reproductive age (12 to 49 years) in a rural setting in northeast Brazil. A total of 734 women were eligible; 592 (80.7%) had initiated sexual life and were included. Women were examined for the presence of an STI. Socio-economic variables, sexual history, and behaviour were assessed through a structured questionnaire. Laboratory testing included: polymerase chain reaction for human papillomavirus (HPV); ligase chain reaction for Chlamydia trachomatis and Neisseria gonorrhoeae; VDRL and FTA-ABS for Treponema pallidum; analysis of wet mounts, gram stain and Pap smears for Trichomonas vaginalis; and ELISA for HIV.Results: At least one STI was present in 112 (19.6%) of the women. In logistic regression analysis, a previous visit to a Pap smear clinic was protective against an STI (OR=0.26; IC 95%: 0.12-0.57). The following variables were independently associated with STIs: ≥3 partners in life (2.35; 1.32-4.17); first pregnancy <16 years of age (2.28; 1.09-4.78); not knowing if partner had another partner (3.56; 1.09-11.62).Conclusions: The protective and risk factors identified can guide the implementation of gender- and age-specific control programs in rural northeast Brazil. Offering a simple preventive measure (Pap smear collection), usually done by a nurse in this setting, may be a useful opportunity for diagnosis and treatment of curable STIs, without considerable additional costs.